(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers the phenomenon of aggression in the context of human nature. Such concepts as aggression and aggressiveness are considered, the urgency of this phenomenon and its conditioned factors are determined, the methods to determine the level of aggressiveness among modern youth are conducted. Factors of aggressive behavior among teenagers are described. Notion such as «cyberbullying» are explained. The main types of aggression have been defined and the main functions and types of aggressive behavior in teenagers have been identified. Factors causing the increase in the level of aggressiveness are also noted. The results of the research between boys and girls are demonstrated. Psychological and pedagogical recommendations on their identification and prevention. were proposed and developed.